Angiotensin II regulates phosphorylation of actin‐associated proteins in human podocytes. Issue 11 (2nd August 2017) - Schenk, Laura K.; Möller‐Kerutt, Annika; Klosowski, Rafael; Wolters, Dirk; Schaffner‐Reckinger, Elisabeth; Weide, Thomas; Pavenstädt, Hermann; Vollenbröker, Beate
Abstract : Within the kidney, angiotensin II (AngII) targets different cell types in the vasculature, tubuli, and glomeruli. An important part of the renal filtration barrier is composed of podocytes with their actin‐rich foot processes. In this study, we used stable isotope labeling with amino acids in cell culture coupled to mass spectrometry to characterize relative changes in the phosphoproteome of human podocytes in response to short‐term treatment with AngII. In 4 replicates, we identified a total of 17, 956 peptides that were traceable to 2081 distinct proteins. Bioinformatic analyses revealed that among the increasingly phosphorylated peptides are predominantly peptides that are related to actin filaments, cytoskeleton, lamellipodia, mammalian target of rapamycin, and MAPK signaling. Among others, this screening approach highlighted the increased phosphorylation of actin‐bundling protein, l ‐plastin (LCP1). AngII‐dependent phosphorylation of LCP1 in cultured podocytes was mediated by the kinases ERK, p90 ribosomal S6 kinase, PKA, or PKC. LCP1 phosphorylation increased filopodia formation. In addition, treatment with AngII led to LCP1 redistribution to the cell margins, membrane ruffling, and formation of lamellipodia. Our data highlight the importance of AngII‐triggered actin cytoskeleton‐associated signal transduction in podocytes.—Schenk, L. K., Möller‐Kerutt, A., Klosowski, R., Wolters, D., Schaffner‐Reckinger, E., Weide, T., Pavenstädt, H., Vollenbröker, B. Angiotensin II regulates phosphorylation of actin‐associated proteins in human podocytes. FASEB J. 31, 5019–5035 (2017). www.fasebj.org